Effectiveness of high-intensity interval training on the mental and physical health of people with chronic schizophrenia - Wu MH (Dove Medical Press, 2015)
Meng Hsiu Wu,1,2 Chin Pang Lee,1–3 Shih Chieh Hsu,1,3 Chia Ming Chang,1,3 Ching Yen Chen1–3 1Department of Psychiatry, Chang Gung Memorial Hospital, Linkou, Taiwan; 2Men’s Health Center, Chang Gung Memorial Hospital, Linkou, Taiwan; 3School of Medicine, Chang Gung University, Taoyuan, Taiwan Background: Low-volume high-intensity interval training (HIIT) is emerging as a time-efficient exercise strategy for improving cardiorespiratory fitness and for controlling blood sugar levels and hypertension. In addition, patient acceptance of HIIT may improve adherence to exercise programs. This study evaluated the effectiveness of HIIT for improving the mental and physical health of people with chronic schizophrenia. Methods: Twenty patients attending a psychiatric day care unit volunteered for an 8-week program of HIIT. Blood pressure, resting heart rate, body weight, body mass index, waist and hip circumference, and waist-to-hip ratio were measured weekly. The Positive and Negative Syndrome Scale score was recorded at baseline and at the end of the study. Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) scores were recorded every 2 weeks. Results: Statistically significant changes occurred in the physical and mental parameters measured in the 18 patients who completed the study. Body weight, body mass index, resting heart rate, and pulse pressure decreased significantly. Mean arterial pressure and diastolic blood pressure increased significantly. Mental health scores improved, with the Negative Scale score decreasing from 31.17±5.95 to 27.78±3.57 (P<0.01) and the General Psychopathology Scale score from 14.28±2.16 to 13.00±1.72 (P<0.01). Positive Scale scores changed, but not significantly, from 12.28±2.27 to 12.33±2.00 (P=0.729). Scores on the BDI (from 19.56±15.28 to 15.89±14.33, P<0.001) and BAI (from 13.67±13.83 to 10.06±11.18, P=0.003) both improved significantly. Conclusion: This study demonstrated that HIIT has positive effects on the physical and mental health of patients with chronic schizophrenia. Keywords: schizophrenia, exercise, depression, anxiety, body weight, blood pressure